2011
DOI: 10.1371/journal.pone.0024913
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Statistical Analysis Techniques Corroborate Intratumor Heterogeneity in Imaging Mass Spectrometry Datasets of Myxofibrosarcoma

Abstract: MALDI mass spectrometry can generate profiles that contain hundreds of biomolecular ions directly from tissue. Spatially-correlated analysis, MALDI imaging MS, can simultaneously reveal how each of these biomolecular ions varies in clinical tissue samples. The use of statistical data analysis tools to identify regions containing correlated mass spectrometry profiles is referred to as imaging MS-based molecular histology because of its ability to annotate tissues solely on the basis of the imaging MS data. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
132
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(132 citation statements)
references
References 39 publications
0
132
0
Order By: Relevance
“…MSI has several key characteristics that make it well suited to this task; it is an untargeted analysis that can simultaneously analyze hundreds of molecular ions, it can be directly applied to tissue sections, it is inexpensive, and it is fast. Several previous studies have reported MSI's ability to uncover tumor subpopulations in histologically identical regions of tumor tissue (5,20,21). Here we have used dimensionality reduction based on t-SNE followed by bisecting k-means clustering to automatically segment the tumor-specific MSI data from a patient series into an optimum number of subpopulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSI has several key characteristics that make it well suited to this task; it is an untargeted analysis that can simultaneously analyze hundreds of molecular ions, it can be directly applied to tissue sections, it is inexpensive, and it is fast. Several previous studies have reported MSI's ability to uncover tumor subpopulations in histologically identical regions of tumor tissue (5,20,21). Here we have used dimensionality reduction based on t-SNE followed by bisecting k-means clustering to automatically segment the tumor-specific MSI data from a patient series into an optimum number of subpopulations.…”
Section: Discussionmentioning
confidence: 99%
“…This approach was based on the consensus of five different linear multivariate methods (20) to locate tumor subpopulations, but required the user to prespecify the number of subpopulations. The resulting cluster data were then compared with the clinical data to assess their statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…[35] 2.2 Protocol-specific solutions 2.2.1 10 mM citric acid monohydrate pH 6 [29,36] ▪ 1.05 g citric acid monohydrate (Sigma-Aldrich, Japan) ▪ Dissolve in 480 mL H 2 O ▪ pH to 6.0 using 1 M NaOH (~13 mL) (Merck, Darmstadt, Germany) ▪ Make up volume to 500 mL with H 2 O 2.2.2 100 mM ammonium bicarbonate (NH 4 [32] ▪ 0.4 pmol/mL angiotensin I [34][35][36][37][38][39][40][41][42][43] ( Figure 1. Protocol for mapping the distribution and determining the identity of tryptic peptides generated in situ.…”
Section: Chemicals Consumables and Equipmentmentioning
confidence: 99%
“…NB: Although multivariate statistics are best used to select peaks of interest, [12,41,42] to keep the workflow as straightforward as possible, peak selection here is manual only and based on operator visualized ion intensity maps for peptides of interest. NB: Steps 6.1 to 6.5 use flexImaging NB: Steps 6.6 onwards use in-house data processing 6.1 When the MALDI-IMS data set loads completely in flexImaging (step 5.10), a sum spectrum will be generated in the Spectrum Display window.…”
Section: Maldi-ims Cancer-specific Peptide Visualization and Calculatmentioning
confidence: 99%
“…Imaging MS-based molecular histology has been used to differentiate between histologically overlapping/identical tumors [6], found evidence of intratumor heterogeneity that could indicate clonal development [6][7][8] and revealed altered protein expression at tumor interface zones [9,10]. These capabilities offer enormous potential to investigate biomolecular changes that occur prior to (or without) morphological change, or those for which a molecular specific stain is unavailable.…”
Section: Introductionmentioning
confidence: 99%